Dataset (Antarctic Oscillation: Its Influence on the Interannual Variability of Precipitation in the Indian Monsoon Region) - Campos Zuñiga, Paula Mayela (2025)
Data used in the analysis presented in the article “Antarctic Oscillation: Its Influence on the Interannual Variability of Precipitation in the Indian Monsoon Region”